Fluid mud consolidation delayed by extracellular polymer substances. Issue 19 (2nd October 2018) - Pang, Qixiu; Zhang, Ruibo; Wen, Chunpeng; Han, Peipei
ABSTRACT: A strain of bacterium identified as Burkholderia vietnamiensis was newly isolated and screened from mud deposited in a harbour basin. The effects of B. vietnamiensis on the fluid mud consolidation and the extracellular polymer substances (EPS) secreted by the microorganisms were examined in laboratory experiments. The experiments revealed the important characteristics of the EPS and their critical contents for nautical-depth applications. The self-weight consolidations in the settling and permeability regimes were best predicated by an exponential equation and a logarithmic equation, respectively. EPS cannot change the trend of sediment settling and consolidation, but its content is negatively correlated with the velocity of sediment consolidation. EPS with high polysaccharide/protein ratio is a potential reference to select bacteria for nautical-depth applications. The critical EPS content that would effectively extend the usage time of nautical depths was estimated as 2.34 g/l.